Consumption of baby kale increased cytochrome P450 1A2 (CYP1A2) activity and influenced bilirubin metabolism in a randomized clinical trial. (January 2020) - Charron, Craig S.; Novotny, Janet A.; Jeffery, Elizabeth H.; Kramer, Matthew; Ross, Sharon A.; Seifried, Harold E.
Graphical abstract: Highlights: Kale consumption increased CYP1A2 activity in adult humans. CYP1A2 activity was generally higher in men than in women. Kale consumption decreased conjugated bilirubin by 54.5% by day 15. Abstract: Brassica vegetables may modulate cancer risk by regulation of xenobiotic metabolizing enzymes (XMEs). In a randomized crossover study, the effect of kale consumption on CYP1A2, CYP2A6, XO, and NAT2 activity was determined by urinary caffeine metabolite ratios, UGT1A1 activity by serum bilirubin concentrations, and GSTA protein and GST activity in blood by ELISA. Adults (n = 25) consumed a basal diet supplemented with kale and radish for 14 days or control vegetables. The kale diet increased CYP1A2 activity by 16.4% on day 8 and 15.2% on day 15 compared to control. Conjugated bilirubin was reduced by the kale diet, decreasing from 19.4 to 14.3 to 9.5% of total bilirubin on days 1, 8, and 15, respectively, which may be explained by induction of MRP2. Other XMEs were not affected by diet. The implications of these results for cancer risk will be clarified as the functions of these XMEs become better understood.